Implementasi Teori Konstruktivisme Ki Hajar Dewantara Dalam Pembelajaran Pendidikan Agama Islam Di SMKN 1 Kediri - Muhammad Syamsul ‘Arif; Abbas Sofwan Matla'il Fajar (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Islamic Religious Education (IRE) in vocational schools faces challenges in relating teaching materials to the diverse realities of students' lives. Therefore, a contextual and student-centered pedagogical approach is needed. This study aims to examine the application of Ki Hajar Dewantara's constructivism theory in IRE learning at SMKN 1 Kediri, as well as its practical meaning and implementation in the classroom context.This research uses a descriptive qualitative approach with observation, interview, and documentation techniques. The focus of the study is directed at the main principles of Dewantara's constructivism, such as the tri N concept and the application of the Tut Wuri Handayani philosophy. The findings of this study indicate that the application of Dewantara's constructivism model significantly improves student engagement and PAI learning outcomes. This is achieved through learning that is more relevant, contextual, and encourages active student participation. However, challenges remain, particularly in terms of teacher readiness and limited resources to support this approach optimally. This research contributes to the development of contextual learning theory in Islamic education, particularly by emphasizing the relevance of a local constructivism approach based on cultural values and national educational philosophy. These findings can serve as a basis for developing a more adaptive and transformative PAI learning model in vocational education settings..